The Impact of Web-Based Cognitive-Behavioral Therapy on Pain Self-Efficacy in Patients with Rheumatoid Arthritis - Omidvar, Rahil; Nayyeri, Mahdi; Teimoori, Saeed (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  This study aims to assess the effectiveness of web-based cognitive-behavioral therapy (CBT) in enhancing pain self-efficacy among patients diagnosed with rheumatoid arthritis (RA), a chronic condition characterized by significant pain and functional limitations.Methods and Materials:  Employing a quasi-experimental design, the study recruited adult RA patients aged 30-60 years from specialized clinics in Mashhad, Iran. Participants were randomly assigned to either the intervention group, which received web-based CBT sessions focused on managing pain and improving self-efficacy, or the control group, which received no such intervention. The intervention consisted of eight sessions designed to educate patients on pain management, cognitive restructuring, and coping strategies. Data on pain self-efficacy were collected at three points: pre-intervention, immediately post-intervention, and at a follow-up session using the Pain Self-Efficacy Questionnaire (PSEQ). Data were analyzed with analysis of variance with repeated measurements and post-hoc tests using SPSS-22.Findings:  Statistical analysis revealed significant improvements in pain self-efficacy scores in the intervention group compared to the control group at post-test and follow-up stages (p